(* Title: HOL/Lambda/Eta.thy
Author: Tobias Nipkow and Stefan Berghofer
Copyright 1995, 2005 TU Muenchen
*)
header {* Eta-reduction *}
theory Eta imports ParRed begin
subsection {* Definition of eta-reduction and relatives *}
primrec
free :: "dB => nat => bool"
where
"free (Var j) i = (j = i)"
| "free (s \<degree> t) i = (free s i \<or> free t i)"
| "free (Abs s) i = free s (i + 1)"
inductive
eta :: "[dB, dB] => bool" (infixl "\<rightarrow>\<^sub>\<eta>" 50)
where
eta [simp, intro]: "\<not> free s 0 ==> Abs (s \<degree> Var 0) \<rightarrow>\<^sub>\<eta> s[dummy/0]"
| appL [simp, intro]: "s \<rightarrow>\<^sub>\<eta> t ==> s \<degree> u \<rightarrow>\<^sub>\<eta> t \<degree> u"
| appR [simp, intro]: "s \<rightarrow>\<^sub>\<eta> t ==> u \<degree> s \<rightarrow>\<^sub>\<eta> u \<degree> t"
| abs [simp, intro]: "s \<rightarrow>\<^sub>\<eta> t ==> Abs s \<rightarrow>\<^sub>\<eta> Abs t"
abbreviation
eta_reds :: "[dB, dB] => bool" (infixl "-e>>" 50) where
"s -e>> t == eta^** s t"
abbreviation
eta_red0 :: "[dB, dB] => bool" (infixl "-e>=" 50) where
"s -e>= t == eta^== s t"
notation (xsymbols)
eta_reds (infixl "\<rightarrow>\<^sub>\<eta>\<^sup>*" 50) and
eta_red0 (infixl "\<rightarrow>\<^sub>\<eta>\<^sup>=" 50)
inductive_cases eta_cases [elim!]:
"Abs s \<rightarrow>\<^sub>\<eta> z"
"s \<degree> t \<rightarrow>\<^sub>\<eta> u"
"Var i \<rightarrow>\<^sub>\<eta> t"
subsection {* Properties of @{text "eta"}, @{text "subst"} and @{text "free"} *}
lemma subst_not_free [simp]: "\<not> free s i \<Longrightarrow> s[t/i] = s[u/i]"
by (induct s arbitrary: i t u) (simp_all add: subst_Var)
lemma free_lift [simp]:
"free (lift t k) i = (i < k \<and> free t i \<or> k < i \<and> free t (i - 1))"
apply (induct t arbitrary: i k)
apply (auto cong: conj_cong)
done
lemma free_subst [simp]:
"free (s[t/k]) i =
(free s k \<and> free t i \<or> free s (if i < k then i else i + 1))"
apply (induct s arbitrary: i k t)
prefer 2
apply simp
apply blast
prefer 2
apply simp
apply (simp add: diff_Suc subst_Var split: nat.split)
done
lemma free_eta: "s \<rightarrow>\<^sub>\<eta> t ==> free t i = free s i"
by (induct arbitrary: i set: eta) (simp_all cong: conj_cong)
lemma not_free_eta:
"[| s \<rightarrow>\<^sub>\<eta> t; \<not> free s i |] ==> \<not> free t i"
by (simp add: free_eta)
lemma eta_subst [simp]:
"s \<rightarrow>\<^sub>\<eta> t ==> s[u/i] \<rightarrow>\<^sub>\<eta> t[u/i]"
by (induct arbitrary: u i set: eta) (simp_all add: subst_subst [symmetric])
theorem lift_subst_dummy: "\<not> free s i \<Longrightarrow> lift (s[dummy/i]) i = s"
by (induct s arbitrary: i dummy) simp_all
subsection {* Confluence of @{text "eta"} *}
lemma square_eta: "square eta eta (eta^==) (eta^==)"
apply (unfold square_def id_def)
apply (rule impI [THEN allI [THEN allI]])
apply (erule eta.induct)
apply (slowsimp intro: subst_not_free eta_subst free_eta [THEN iffD1])
apply safe
prefer 5
apply (blast intro!: eta_subst intro: free_eta [THEN iffD1])
apply blast+
done
theorem eta_confluent: "confluent eta"
apply (rule square_eta [THEN square_reflcl_confluent])
done
subsection {* Congruence rules for @{text "eta\<^sup>*"} *}
lemma rtrancl_eta_Abs: "s \<rightarrow>\<^sub>\<eta>\<^sup>* s' ==> Abs s \<rightarrow>\<^sub>\<eta>\<^sup>* Abs s'"
by (induct set: rtranclp)
(blast intro: rtranclp.rtrancl_into_rtrancl)+
lemma rtrancl_eta_AppL: "s \<rightarrow>\<^sub>\<eta>\<^sup>* s' ==> s \<degree> t \<rightarrow>\<^sub>\<eta>\<^sup>* s' \<degree> t"
by (induct set: rtranclp)
(blast intro: rtranclp.rtrancl_into_rtrancl)+
lemma rtrancl_eta_AppR: "t \<rightarrow>\<^sub>\<eta>\<^sup>* t' ==> s \<degree> t \<rightarrow>\<^sub>\<eta>\<^sup>* s \<degree> t'"
by (induct set: rtranclp) (blast intro: rtranclp.rtrancl_into_rtrancl)+
lemma rtrancl_eta_App:
"[| s \<rightarrow>\<^sub>\<eta>\<^sup>* s'; t \<rightarrow>\<^sub>\<eta>\<^sup>* t' |] ==> s \<degree> t \<rightarrow>\<^sub>\<eta>\<^sup>* s' \<degree> t'"
by (blast intro!: rtrancl_eta_AppL rtrancl_eta_AppR intro: rtranclp_trans)
subsection {* Commutation of @{text "beta"} and @{text "eta"} *}
lemma free_beta:
"s \<rightarrow>\<^sub>\<beta> t ==> free t i \<Longrightarrow> free s i"
by (induct arbitrary: i set: beta) auto
lemma beta_subst [intro]: "s \<rightarrow>\<^sub>\<beta> t ==> s[u/i] \<rightarrow>\<^sub>\<beta> t[u/i]"
by (induct arbitrary: u i set: beta) (simp_all add: subst_subst [symmetric])
lemma subst_Var_Suc [simp]: "t[Var i/i] = t[Var(i)/i + 1]"
by (induct t arbitrary: i) (auto elim!: linorder_neqE simp: subst_Var)
lemma eta_lift [simp]: "s \<rightarrow>\<^sub>\<eta> t ==> lift s i \<rightarrow>\<^sub>\<eta> lift t i"
by (induct arbitrary: i set: eta) simp_all
lemma rtrancl_eta_subst: "s \<rightarrow>\<^sub>\<eta> t \<Longrightarrow> u[s/i] \<rightarrow>\<^sub>\<eta>\<^sup>* u[t/i]"
apply (induct u arbitrary: s t i)
apply (simp_all add: subst_Var)
apply blast
apply (blast intro: rtrancl_eta_App)
apply (blast intro!: rtrancl_eta_Abs eta_lift)
done
lemma rtrancl_eta_subst':
fixes s t :: dB
assumes eta: "s \<rightarrow>\<^sub>\<eta>\<^sup>* t"
shows "s[u/i] \<rightarrow>\<^sub>\<eta>\<^sup>* t[u/i]" using eta
by induct (iprover intro: eta_subst)+
lemma rtrancl_eta_subst'':
fixes s t :: dB
assumes eta: "s \<rightarrow>\<^sub>\<eta>\<^sup>* t"
shows "u[s/i] \<rightarrow>\<^sub>\<eta>\<^sup>* u[t/i]" using eta
by induct (iprover intro: rtrancl_eta_subst rtranclp_trans)+
lemma square_beta_eta: "square beta eta (eta^**) (beta^==)"
apply (unfold square_def)
apply (rule impI [THEN allI [THEN allI]])
apply (erule beta.induct)
apply (slowsimp intro: rtrancl_eta_subst eta_subst)
apply (blast intro: rtrancl_eta_AppL)
apply (blast intro: rtrancl_eta_AppR)
apply simp;
apply (slowsimp intro: rtrancl_eta_Abs free_beta
iff del: dB.distinct simp: dB.distinct) (*23 seconds?*)
done
lemma confluent_beta_eta: "confluent (sup beta eta)"
apply (assumption |
rule square_rtrancl_reflcl_commute confluent_Un
beta_confluent eta_confluent square_beta_eta)+
done
subsection {* Implicit definition of @{text "eta"} *}
text {* @{term "Abs (lift s 0 \<degree> Var 0) \<rightarrow>\<^sub>\<eta> s"} *}
lemma not_free_iff_lifted:
"(\<not> free s i) = (\<exists>t. s = lift t i)"
apply (induct s arbitrary: i)
apply simp
apply (rule iffI)
apply (erule linorder_neqE)
apply (rule_tac x = "Var nat" in exI)
apply simp
apply (rule_tac x = "Var (nat - 1)" in exI)
apply simp
apply clarify
apply (rule notE)
prefer 2
apply assumption
apply (erule thin_rl)
apply (case_tac t)
apply simp
apply simp
apply simp
apply simp
apply (erule thin_rl)
apply (erule thin_rl)
apply (rule iffI)
apply (elim conjE exE)
apply (rename_tac u1 u2)
apply (rule_tac x = "u1 \<degree> u2" in exI)
apply simp
apply (erule exE)
apply (erule rev_mp)
apply (case_tac t)
apply simp
apply simp
apply blast
apply simp
apply simp
apply (erule thin_rl)
apply (rule iffI)
apply (erule exE)
apply (rule_tac x = "Abs t" in exI)
apply simp
apply (erule exE)
apply (erule rev_mp)
apply (case_tac t)
apply simp
apply simp
apply simp
apply blast
done
theorem explicit_is_implicit:
"(\<forall>s u. (\<not> free s 0) --> R (Abs (s \<degree> Var 0)) (s[u/0])) =
(\<forall>s. R (Abs (lift s 0 \<degree> Var 0)) s)"
by (auto simp add: not_free_iff_lifted)
subsection {* Eta-postponement theorem *}
text {*
Based on a paper proof due to Andreas Abel.
Unlike the proof by Masako Takahashi \cite{Takahashi-IandC}, it does not
use parallel eta reduction, which only seems to complicate matters unnecessarily.
*}
theorem eta_case:
fixes s :: dB
assumes free: "\<not> free s 0"
and s: "s[dummy/0] => u"
shows "\<exists>t'. Abs (s \<degree> Var 0) => t' \<and> t' \<rightarrow>\<^sub>\<eta>\<^sup>* u"
proof -
from s have "lift (s[dummy/0]) 0 => lift u 0" by (simp del: lift_subst)
with free have "s => lift u 0" by (simp add: lift_subst_dummy del: lift_subst)
hence "Abs (s \<degree> Var 0) => Abs (lift u 0 \<degree> Var 0)" by simp
moreover have "\<not> free (lift u 0) 0" by simp
hence "Abs (lift u 0 \<degree> Var 0) \<rightarrow>\<^sub>\<eta> lift u 0[dummy/0]"
by (rule eta.eta)
hence "Abs (lift u 0 \<degree> Var 0) \<rightarrow>\<^sub>\<eta>\<^sup>* u" by simp
ultimately show ?thesis by iprover
qed
theorem eta_par_beta:
assumes st: "s \<rightarrow>\<^sub>\<eta> t"
and tu: "t => u"
shows "\<exists>t'. s => t' \<and> t' \<rightarrow>\<^sub>\<eta>\<^sup>* u" using tu st
proof (induct arbitrary: s)
case (var n)
thus ?case by (iprover intro: par_beta_refl)
next
case (abs s' t)
note abs' = this
from `s \<rightarrow>\<^sub>\<eta> Abs s'` show ?case
proof cases
case (eta s'' dummy)
from abs have "Abs s' => Abs t" by simp
with eta have "s''[dummy/0] => Abs t" by simp
with `\<not> free s'' 0` have "\<exists>t'. Abs (s'' \<degree> Var 0) => t' \<and> t' \<rightarrow>\<^sub>\<eta>\<^sup>* Abs t"
by (rule eta_case)
with eta show ?thesis by simp
next
case (abs r)
from `r \<rightarrow>\<^sub>\<eta> s'`
obtain t' where r: "r => t'" and t': "t' \<rightarrow>\<^sub>\<eta>\<^sup>* t" by (iprover dest: abs')
from r have "Abs r => Abs t'" ..
moreover from t' have "Abs t' \<rightarrow>\<^sub>\<eta>\<^sup>* Abs t" by (rule rtrancl_eta_Abs)
ultimately show ?thesis using abs by simp iprover
qed
next
case (app u u' t t')
from `s \<rightarrow>\<^sub>\<eta> u \<degree> t` show ?case
proof cases
case (eta s' dummy)
from app have "u \<degree> t => u' \<degree> t'" by simp
with eta have "s'[dummy/0] => u' \<degree> t'" by simp
with `\<not> free s' 0` have "\<exists>r. Abs (s' \<degree> Var 0) => r \<and> r \<rightarrow>\<^sub>\<eta>\<^sup>* u' \<degree> t'"
by (rule eta_case)
with eta show ?thesis by simp
next
case (appL s')
from `s' \<rightarrow>\<^sub>\<eta> u`
obtain r where s': "s' => r" and r: "r \<rightarrow>\<^sub>\<eta>\<^sup>* u'" by (iprover dest: app)
from s' and app have "s' \<degree> t => r \<degree> t'" by simp
moreover from r have "r \<degree> t' \<rightarrow>\<^sub>\<eta>\<^sup>* u' \<degree> t'" by (simp add: rtrancl_eta_AppL)
ultimately show ?thesis using appL by simp iprover
next
case (appR s')
from `s' \<rightarrow>\<^sub>\<eta> t`
obtain r where s': "s' => r" and r: "r \<rightarrow>\<^sub>\<eta>\<^sup>* t'" by (iprover dest: app)
from s' and app have "u \<degree> s' => u' \<degree> r" by simp
moreover from r have "u' \<degree> r \<rightarrow>\<^sub>\<eta>\<^sup>* u' \<degree> t'" by (simp add: rtrancl_eta_AppR)
ultimately show ?thesis using appR by simp iprover
qed
next
case (beta u u' t t')
from `s \<rightarrow>\<^sub>\<eta> Abs u \<degree> t` show ?case
proof cases
case (eta s' dummy)
from beta have "Abs u \<degree> t => u'[t'/0]" by simp
with eta have "s'[dummy/0] => u'[t'/0]" by simp
with `\<not> free s' 0` have "\<exists>r. Abs (s' \<degree> Var 0) => r \<and> r \<rightarrow>\<^sub>\<eta>\<^sup>* u'[t'/0]"
by (rule eta_case)
with eta show ?thesis by simp
next
case (appL s')
from `s' \<rightarrow>\<^sub>\<eta> Abs u` show ?thesis
proof cases
case (eta s'' dummy)
have "Abs (lift u 1) = lift (Abs u) 0" by simp
also from eta have "\<dots> = s''" by (simp add: lift_subst_dummy del: lift_subst)
finally have s: "s = Abs (Abs (lift u 1) \<degree> Var 0) \<degree> t" using appL and eta by simp
from beta have "lift u 1 => lift u' 1" by simp
hence "Abs (lift u 1) \<degree> Var 0 => lift u' 1[Var 0/0]"
using par_beta.var ..
hence "Abs (Abs (lift u 1) \<degree> Var 0) \<degree> t => lift u' 1[Var 0/0][t'/0]"
using `t => t'` ..
with s have "s => u'[t'/0]" by simp
thus ?thesis by iprover
next
case (abs r)
from `r \<rightarrow>\<^sub>\<eta> u`
obtain r'' where r: "r => r''" and r'': "r'' \<rightarrow>\<^sub>\<eta>\<^sup>* u'" by (iprover dest: beta)
from r and beta have "Abs r \<degree> t => r''[t'/0]" by simp
moreover from r'' have "r''[t'/0] \<rightarrow>\<^sub>\<eta>\<^sup>* u'[t'/0]"
by (rule rtrancl_eta_subst')
ultimately show ?thesis using abs and appL by simp iprover
qed
next
case (appR s')
from `s' \<rightarrow>\<^sub>\<eta> t`
obtain r where s': "s' => r" and r: "r \<rightarrow>\<^sub>\<eta>\<^sup>* t'" by (iprover dest: beta)
from s' and beta have "Abs u \<degree> s' => u'[r/0]" by simp
moreover from r have "u'[r/0] \<rightarrow>\<^sub>\<eta>\<^sup>* u'[t'/0]"
by (rule rtrancl_eta_subst'')
ultimately show ?thesis using appR by simp iprover
qed
qed
theorem eta_postponement':
assumes eta: "s \<rightarrow>\<^sub>\<eta>\<^sup>* t" and beta: "t => u"
shows "\<exists>t'. s => t' \<and> t' \<rightarrow>\<^sub>\<eta>\<^sup>* u" using eta beta
proof (induct arbitrary: u)
case base
thus ?case by blast
next
case (step s' s'' s''')
then obtain t' where s': "s' => t'" and t': "t' \<rightarrow>\<^sub>\<eta>\<^sup>* s'''"
by (auto dest: eta_par_beta)
from s' obtain t'' where s: "s => t''" and t'': "t'' \<rightarrow>\<^sub>\<eta>\<^sup>* t'" using step
by blast
from t'' and t' have "t'' \<rightarrow>\<^sub>\<eta>\<^sup>* s'''" by (rule rtranclp_trans)
with s show ?case by iprover
qed
theorem eta_postponement:
assumes "(sup beta eta)\<^sup>*\<^sup>* s t"
shows "(beta\<^sup>*\<^sup>* OO eta\<^sup>*\<^sup>*) s t" using assms
proof induct
case base
show ?case by blast
next
case (step s' s'')
from step(3) obtain t' where s: "s \<rightarrow>\<^sub>\<beta>\<^sup>* t'" and t': "t' \<rightarrow>\<^sub>\<eta>\<^sup>* s'" by blast
from step(2) show ?case
proof
assume "s' \<rightarrow>\<^sub>\<beta> s''"
with beta_subset_par_beta have "s' => s''" ..
with t' obtain t'' where st: "t' => t''" and tu: "t'' \<rightarrow>\<^sub>\<eta>\<^sup>* s''"
by (auto dest: eta_postponement')
from par_beta_subset_beta st have "t' \<rightarrow>\<^sub>\<beta>\<^sup>* t''" ..
with s have "s \<rightarrow>\<^sub>\<beta>\<^sup>* t''" by (rule rtranclp_trans)
thus ?thesis using tu ..
next
assume "s' \<rightarrow>\<^sub>\<eta> s''"
with t' have "t' \<rightarrow>\<^sub>\<eta>\<^sup>* s''" ..
with s show ?thesis ..
qed
qed
end